Petting away pre‐exam stress: The effect of therapy dog sessions on student well‐being. (12th March 2018) - Ward‐Griffin, Emma; Klaiber, Patrick; Collins, Hanne K.; Owens, Rhea L.; Coren, Stanley; Chen, Frances S.
Abstract: Recently, many universities have implemented programmes in which therapy dogs and their handlers visit college campuses. Despite the immense popularity of therapy dog sessions, few randomized studies have empirically tested the efficacy of such programmes. The present study evaluates the efficacy of such a therapy dog programme in improving the well‐being of university students. This research incorporates two components: (a) a pre/post within‐subjects design, in which 246 participants completed a brief questionnaire immediately before and after a therapy dog session and (b) an experimental design with a delayed‐treatment control group, in which all participants completed baseline measures and follow‐up measures approximately 10 hr later. Only participants in the experimental condition experienced the therapy dog session in between the baseline and follow‐up measures. Analyses of pre/post data revealed that the therapy dog sessions had strong immediate benefits, significantly reducing stress and increasing happiness and energy levels. In addition, participants in the experimental group reported a greater improvement in negative affect, perceived social support, and perceived stress compared with those in the delayed‐treatment control group. Our results suggest that single, drop‐in, therapy dog sessions have large and immediate effects on students' well‐being, but also that the effects after several hours are small.